2011
DOI: 10.1097/qai.0b013e31821e9a1e
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Human T-Cell Lymphotropic Virus I Infection on Clinical and Immunologic Outcomes in Patients Coinfected With HIV and Hepatitis C Virus

Abstract: Background HIV, hepatitis C (HCV), and human T-cell lymphotropic virus I (HTLV-1) are associated with high global burdens of disease, notably in resource-poor locales. They share similar routes of transmission and cause chronic infections with associated morbidity. We performed a cross-sectional study to assess the impact of HTLV-1 infection on clinical outcomes in HIV/HCV-coinfected patients. Methods We enrolled 102 (72.3%) with HIV/HCV coinfection (Group 1) and 39 (27.7%) triply infected with HIV, HCV, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 27 publications
0
28
1
1
Order By: Relevance
“…In contrast to the Japanese findings, however, two Brazilian studies [22,23] of HCV/HTLV-1 co-infection provide epidemiological and immunological evidence of a higher rate of spontaneous clearance of HCV in patients with HIV/HTLV-1 co-infection as compared to patients harbouring only an HIV/HCV co-infection or an HCV mono-infection. The differences between HCV and HTLV-1 interaction outcomes in these two settings may be due to host genetic factors (e.g., HLA genotypes), study design, or other unmeasured parameters of the study populations.…”
Section: Clinical Implications Of Hcv/htlv-1/2 Co-infectioncontrasting
confidence: 40%
“…In contrast to the Japanese findings, however, two Brazilian studies [22,23] of HCV/HTLV-1 co-infection provide epidemiological and immunological evidence of a higher rate of spontaneous clearance of HCV in patients with HIV/HTLV-1 co-infection as compared to patients harbouring only an HIV/HCV co-infection or an HCV mono-infection. The differences between HCV and HTLV-1 interaction outcomes in these two settings may be due to host genetic factors (e.g., HLA genotypes), study design, or other unmeasured parameters of the study populations.…”
Section: Clinical Implications Of Hcv/htlv-1/2 Co-infectioncontrasting
confidence: 40%
“…27 In a recent study of patients infected with HCV/HIV/HTLV-1/2 in Brazil, we found that those with triple infection had on average lower ALT levels than patients coinfected with HIV/HCV, suggesting lower hepatic inflammation in the former group. 28 …”
Section: Introductionmentioning
confidence: 99%
“…HIV-1 and HTLV-1 co-infection in vivo has also been extensively reported, and it has been suggested that co-infection by the two viruses influences the pathologic progression of both viruses (Bahia et al, 2011; Beilke, 2012; Brites et al, 2009; Pedroso et al, 2011). Because both HIV-1 and HTLV-1 can infect CD4+ T cells, this co-infection may differ from those of HIV-1/herpesviruses in that both viral genomes could co-exist in a single infected cell.…”
Section: Introductionmentioning
confidence: 99%